Intro to React - Tucker, John; Dennison, Justin (Packt Publishing, 2024)
Join Justin and John on a transformative journey into ReactJS. This comprehensive video series starts with an overview of essential JavaScript features and build tools like Webpack, crucial for developing and deploying modern web applications. You'll build a solid foundation to navigate the React ecosystem with confidence. As the series progresses, you'll explore the core concepts of React, understanding the problems it solves and how it enhances front-end development. The instructors provide a detailed overview of the tools and ecosystem used throughout the course, preparing you for hands-on learning. By following a step-by-step approach, you'll learn how to transform a simple JavaScript application using React, showcasing the benefits and efficiencies of this powerful library. In the later episodes, you'll focus on practical implementation. You'll dive into build processes like create-react-app and new JavaScript features from ES2015, including const, let, imports, exports, and destructuring. By the end of the series, you'll master using state and props to manage and streamline your applications, turning them into efficient, scalable React projects. Whether you're a novice or looking to refresh your skills, this series provides a thorough grounding in ReactJS.